Respiratory toxicity of TiO2 nanoparticles after intravenous instillation: an experimental study - Hurbánková, Marta; Volkovová, Katarína; Wimmerová, Soňa; Henčeková, Danica; Moricová, Štefánia (Central European journal of public health, 2018)
OBJECTIVE: Nanomaterials are materials consisting of particles having one or more dimensions smaller than 100 nm. Nanoparticles (NP) have different properties and effects in comparison with the same particle materials of larger size. They can penetrate through various membranes and get from the bloodstream to other organs in the body. Therefore, in our experiment we have dealt with the impact of nanoparticles TiO2 instilled intravenously (i.v.) (to a tail vein of an animal) on the selected parameters of bronchoalveolar lavage (BAL). The aim of our study was to determine whether TiO2 nanoparticles do pass through the vascular system to the respiratory tract, and if so, how they affect the selected inflammatory and cytotoxic parameters of bronchoalveolar lavage. METHODS: Wistar rats were intravenously given a suspension of TiO2 nanoparticles in saline solution. This suspension contained 10% volume of rat serum in dose: 1.0% from LD50 = 0.592 mg/kg of animal body weight. After the time intervals 1, 7, 14 and 28 days, the animals were sacrificed under anaesthesia; bronchoalveolar lavage was performed and the BAL cells were isolated. We have examined these markers: differential count of BAL cells - alveolar macrophages (AM), polymorphonuclear leukocytes (PMNL), lymphocytes (Ly); viability and phagocytic activity of AM; proportion of immature cells and cathepsin D enzyme levels. RESULTS: Regarding the respiratory toxicity of TiO2 nanoparticles we have found that TiO2 nanoparticles are relatively inert. BAL examined parameters (except the immature form of AM) were not significantly changed after 28 days of instillation compared to the control group. We found that the TiO2 nanoparticles used in our study were transferred from the bloodstream to the respiratory tract, but in a 28-day phase after i.v. instillation have been largely eliminated by the defence mechanism from the respiratory tract. CONCLUSIONS: We suggest low biopersistence and relatively rapid elimination of TiO2 nanoparticles from the lung under used experimental conditions.
Keywords: Animals; bronchoalveolární lavážní tekutina; kovové nanočástice; bronchoalveolar lavage; velikost částic; Bronchoalveolar Lavage Fluid; inflammatory and cytotoxic parameters; Administration, Intravenous; Rats, Wistar; Particle Size; intravenózní podání; Titanium; Metal Nanoparticles; intravenous instillation; titan; TiO2 nanoparticles; krysa rodu Rattus; zvířata; Rats; potkani Wistar